Muslim Women's Purchasing Behaviors Toward Modest Activewear in the United States. (July 2021) - Hwang, Chanmi; Kim, Tae Ho
This study examines Muslim women's purchasing behaviors toward modest activewear in the United States and tests the underlying mechanism of intent to purchase activewear, based on the theory of planned behavior (TPB). A sample of veiled Muslim women ( N = 328) participated in this study. Results from structural equation modeling revealed that perceived aesthetic attributes and compatibility with regard to apparel functionality, expressiveness, and aesthetics are significant predictors of attitude toward purchasing activewear. Attitude and subjective norm are significantly related to intent to purchase modest activewear, and religiosity indirectly influences purchase intention through the social norm. This research extends the TPB and contributes to the growing body of research on Muslim consumers' purchasing behavior and to the growing modest apparel market and pro-hijab movement in the industry.